Kedudukan al-Tas‘īr al-Jabarī dalam Tinjauan Kaidah Yutaḥammal al-Ḍarar al-Khāṣ li Daf‘ al-Ḍarar al-‘Ām - Asnawati Patuti; Afia Hafizah; Aisyah Aisyah (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2023)
This research aims to find out and understand the law and position of al-tas‘īr al-jabarī in reviewing the rules of yutaḥammal al-ḍarar al-khāṣ li daf‘i al-ḍarar al-‘ām. The type of research used is descriptive qualitative in the form of library research with a normative and sociological approach. The research results show that al-tas'īr al-jabarī is a government policy in the form of intervention to set certain prices for goods, food and services, which the public is obliged to comply with. Al-tas‘īr al-jabarī has different positions depending on market conditions. Under normal conditions, the al-tas‘īr al-jabarī policy is not needed so its position returns to its original law, namely that it cannot be carried out. However, in abnormal conditions, the al-tas'īr al-jabarī policy can be a solution so that it can be done to prevent al-ḍarar al-'ām which will befall a large number of people, even though it has to bear the al-ḍarar al-khāṣ which will befall certain individuals or groups as a result of al-tas'īr al-jabarī's policies.